Desain Sistem Retrofit Library Pada Pengembangan Rest Client - Ventje Lumentut; Kieven Karundeng; Marike Kondoj; Steven Runtuwene; Stephy B. Walukow; Johan Pongoh (Pusat Penelitian dan Pengabdian Kepada Masyarakat Politeknik Negeri Manado, 2022)
To access a website-based information system, users must open it via a web browser. Limited access via a web browser makes it difficult for users to access information in real time. For this reason, it is necessary to develop an Android-based system by implementing retrofit libraries and rest clients to make it easier to access an information system. the test was carried out to access the research and community service system at the Manado State Polytechnic. Using the retrofit library doesn't need to create its own methods to use the rest client api, this library provides a framework for interacting with the api by sending requests using okhttp.